2022
DOI: 10.1002/slct.202103943
|View full text |Cite|
|
Sign up to set email alerts
|

Chemoselectivity in the Transannulaction of 1,2,3‐Thiadiazoles and Alk‐2‐enenitriles: Specific Synthesis of 3‐(Alk‐1‐enyl)isothiazoles

Abstract: 1,2,3‐Thiadiazoles are precursors of thioacylcarbenes and thioketenes and show various reactions with unsaturated compounds. The rhodium‐catalyzed reactions of 1,2,3‐thiadiazoles and alk‐2‐enenitriles, including alkyl, aryl, and heteroaryl acrylonitriles, have been investigated, showing chemospecific reactivity to generate 3‐vinylisothiazole derivatives via the (3+2) transannulation between the cyano group of alk‐2‐enenitriles and generated thioacylcarbenes. (Z)‐Cinnamonitriles are less active than (E)‐cinnamo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…The catalytic (3 + n) annulations of a-thioacyl carbenes, derived from 1,2,3-thiadiazoles under Rh(I) or Ir(I) catalysis, have served as an efficient tool for constructing thiacycles. [1][2][3][4][5][6] The advances in annulations with substrates containing C-X (X = heteroatom) multiple bonds indicated that the reactivity of a-thioacyl carbenes differed significantly as the electronic properties of substrates changed. [4][5][6] For example, in their (3 + 2) annulations with 1-phosphaalkynes, 4 a-thioacyl carbenes showed normal reactivity (nucleophilic sulfur and electrophilic carbenic carbon).…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…The catalytic (3 + n) annulations of a-thioacyl carbenes, derived from 1,2,3-thiadiazoles under Rh(I) or Ir(I) catalysis, have served as an efficient tool for constructing thiacycles. [1][2][3][4][5][6] The advances in annulations with substrates containing C-X (X = heteroatom) multiple bonds indicated that the reactivity of a-thioacyl carbenes differed significantly as the electronic properties of substrates changed. [4][5][6] For example, in their (3 + 2) annulations with 1-phosphaalkynes, 4 a-thioacyl carbenes showed normal reactivity (nucleophilic sulfur and electrophilic carbenic carbon).…”
mentioning
confidence: 99%
“…[1][2][3][4][5][6] The advances in annulations with substrates containing C-X (X = heteroatom) multiple bonds indicated that the reactivity of a-thioacyl carbenes differed significantly as the electronic properties of substrates changed. [4][5][6] For example, in their (3 + 2) annulations with 1-phosphaalkynes, 4 a-thioacyl carbenes showed normal reactivity (nucleophilic sulfur and electrophilic carbenic carbon). 1,2 However, when nitriles were reacted, 3b,c,5c complete umpolung reactivity (electrophilic sulfur and nucleophilic carbenic carbon) was observed.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…[16 -19] 1,2-Diaryl-2,3-dihydro-1H-1,5-benzodiazepines were readily prepared from o-phenylenediamine with chalcones [10] and 1phenylbut-2-en-1-one [20] in the presence of piperidine followed by treatment with acetic acid. When we conducted annulation of 1,2,3-thiadiazoles with alk-2enenitriles, [21] we also attempted annulation of 1,2,3thiadiazoles with imines, including 2,3-dihydro-1H-1,5-benzodiazepines as a class of cyclic imines. Although no annulation products were observed, a benzimidazole ring contraction product was isolated in low yield under the action of the Rh catalyst.…”
Section: Introductionmentioning
confidence: 99%